Clinical observation of desloratadine combined with omalizumab in the treatment of chronic spontaneous urticaria - Zhiwei SHANG; Haixia FENG; Bingjie ZHAO; Liye XIA (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
Objective To observe the clinical efficacy and safety of desloratadine combined with omalizumab in the treatment of chronic spontaneous urticaria (CSU). Methods A total of 60 patients with CSU were randomly divided into the observation and the control groups, 30 patients per group. The observation group was treated with oral desloratadine tablet (5 mg, qd) and subcutaneous injection of omalizumab (300 mg, q4w) for 12 weeks, while the control group was treated with oral desloratadine tablet (5 mg, qd) alone. The clinical efficacy and adverse reactions were assessed after the treatment. All patients were followed up for 3 months to observe the recurrence. Results The total effective rates were 90.00% in the observation group and 63.33% in the control group (P<0.05). The recurrence rate was significant lower in the observation group than in the controls (14.81% vs. 57.89%, P<0.05). Following the treatment, serum IgE levels were significantly elevated in the observation group (P<0.05 vs. pretreatment), while the serum IgE levels were comparable before and after the treatment in the control group. No severe adverse reactions occurred in either group. Conclusions Combination of oral desloratadine tablet and subcutaneous injection of omalizumab is effective and safe, with a lower recurrence rate, for chronic spontaneous urticaria. This combination therapy can be a new option for chronic spontaneous urticaria.